1999
DOI: 10.1002/(sici)1096-9861(19990517)407:4<555::aid-cne7>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Projections of the median raphe nucleus in the rat

Abstract: No previous report in any species has examined comprehensively the projections of the median raphe (MR) nucleus with modern tracing techniques. The present report represents an in depth analysis of the projections of MR by use of the anterograde anatomical tracer Phaseolus vulgaris‐leucoagglutinin. MR fibers descend along the midline within the brainstem and mainly ascend within the medial forebrain bundle in the forebrain. MR fibers distribute densely to the following brainstem/forebrain sites: caudal raphe n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
248
2
9

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 475 publications
(296 citation statements)
references
References 167 publications
(149 reference statements)
37
248
2
9
Order By: Relevance
“…On the other hand, although LHb projects strongly to DR (Vertes et al, 1999), we found that DR serotonin neurons (andVTA and SNcdopamine neurons) receive few monosynaptic inputs from LHb. Recent studies found that the rostromedial tegmental nucleus (RMTg)relays inputs from LHb to DR as well as to dopamine neurons (Jhou et al, 2009).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…On the other hand, although LHb projects strongly to DR (Vertes et al, 1999), we found that DR serotonin neurons (andVTA and SNcdopamine neurons) receive few monosynaptic inputs from LHb. Recent studies found that the rostromedial tegmental nucleus (RMTg)relays inputs from LHb to DR as well as to dopamine neurons (Jhou et al, 2009).…”
Section: Discussionmentioning
confidence: 55%
“…The reciprocal connection between DR and VTA hasbeen reported (Geisler and Zahm, 2005; Vertes et al, 1999) but which cell types contribute to these interactions is unknown. In particular, while serotonergicregulation of VTA dopamine neurons was confirmed by multiple methods (Boureau and Dayan, 2011), projectionsfrom dopamine to serotonin neurons have remained unclear(Ferreira et al, 2008; Kalén et al, 1988).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, developmental SSRI exposure may differentially alter the establishment of specific inputs onto DR and MR 5-HT neurons (Dorocic et al, 2014; Lechin et al, 2006), including those from local GABAergic interneurons (Challis et al, 2013; Rood et al, 2014). Finally, MR and DR send reciprocal projections to each other (Bang et al, 2012; Muzerelle et al, 2014; Vertes et al, 1999), and developmental interference with the establishment of interconnectivity can lead to permanently altered relative 5-HTergic activity. Together these mechanisms might converge on permanently altering the balance between DR and MR 5-HTergic activity and provide a pathway for environmental and genetic factors to guide, influence or perturb 5-HTergic system development.…”
Section: Discussionmentioning
confidence: 99%
“…Retrograde labeling is detected in the raphe nuclei following injections of retrograde tracers into the LHb (Herkenham and Nauta, 1977; Li et al, 1993; Felton et al, 1999; Yetnikoff et al, 2015; Muzerelle et al, 2016) and strong bilateral projections from the median raphe to the LHb have been mapped by autoradiographic demonstration of anterogradely transported tritiated amino acids (Conrad and Pfaff, 1976a; Vertes and Martin, 1988) and PHA-L (Vertes et al, 1999). In contrast, Vertes (1991) was able to detect with PHA-L only a light ipsilateral projection to the LHb from the DR. Morin and Meyer-Bernstein (1999), studying the hamster, have made the interesting point that the MHb has a moderately dense serotonin terminal plexus, but does not receive significant input from the median or dorsal raphe, whereas LHb, which exhibits little serotoninergic immunoreactivity, receives substantial input from the raphe nuclei (mainly median raphe) presumably of a non-serotoninergic phenotype.…”
Section: Afferent Connectionsmentioning
confidence: 99%